THE RELATIONSHIP BETWEEN BODY SHAMING AND STRESS LEVELS OF THE NINTH-GRADE STUDENTS AT SMPN 4 BOJONEGORO - Saifudin, Moh.; Sholikah, Siti; Apreliani, Eska Wulan (Universitas Airlangga, 2022)
Introduction: Adolescence is marked by changes in growth and development that occur very rapidly. Adolescents will experience stages towards social and economic independence, identity building, acquisition of skills for adult life, and the ability to negotiate. Body shaming, weight shaming, or harassment based on appearance can be described as mocking or humiliating someone based on their physical appearance. The study aimed to determine the relationship between body shaming behaviour and the stress levels of the ninth graders at SMP N 4 Bojonegoro. Methods: The design of this research was a cross-sectional analysis. The population was 80 ninth graders obtained by using a purposive sampling technique. The students were experiencing body shaming. The research data were taken using the Body-Shaming questionnaire to measure body shaming behaviour and the Depression Anxiety Stress Scale (DASS) 42 questionnaire to measure stress levels. Results: The results showed that 9 out of 11 students (81.8%) who experienced severe body shaming behaviour had extreme stress levels, 37 out of 38 students (97.4%) students who participated in proper body shaming behaviour had moderate stress levels, 18 out of 31 students (58.1%) who experienced mild body shaming behaviour had mild stress levels. Based on the results of the data above, a statistical test was obtained with a significance value of p sign = 0.01 (p <0.05). Conclusions: It can be concluded that there is a relationship between body shaming behaviour and the stress levels of the ninth graders at SMP N 4 Bojonegoro.